Challenges and Advances in Managing Heatstroke Among Military Forces: A Review of Recent Studies - Fransiska Pratiwi, Ardita (Syntax Literate, 2026)
Exertional heat stroke (EHS) remains a persistent threat to military operations, necessitating a shift from traditional thermal load perspectives toward a "heat sepsis" mechanism characterized by systemic inflammation and multiorgan injury. Recent advances emphasize the importance of objective risk assessment through standardized Heat Tolerance Tests (HTTs) and the use of biomarkers like plasma homocysteine and copeptin to gauge physiological readiness. Effective prevention strategies now integrate 7–14 day acclimatization protocols, real-time environmental monitoring via wearable sensors, and proactive hydration. Furthermore, immediate acute management using Ice-Cold Water Immersion (ICWI) has been proven to achieve superior cooling rates and reduce morbidity, highlighting the need for a multidisciplinary approach that bridges physiology, technology, and education to safeguard service members.